Mechanisms of Heavy Metal Immobilisation using Geopolymerisation Techniques – A review - Vu, Tran Huyen; Gowripalan, Nadarajah (Journal of Advanced Concrete Technology, 2018)
Every year, substantial amount of waste materials containing toxic substances is produced throughout the world, which causes serious damage to the environment and poses threat to human health. Among available techniques of immobilisation of toxic elements in harmful by-products, geopolymerisation is considered as an effective approach to deal with many environmental issues. Geopolymer binders have long been recognised to have great potential in immobilisation of hazardous wastes due to its advantages over Portland cement based binders. A profound knowledge of how hazardous elements are immobilised by geopolymer binders is necessary for achieving effective waste management strategies. This paper provides some important aspects of geopolymer materials regarding the immobilisation mechanisms and factors influencing the immobilisation efficiency, which are necessary to carry out further research on addressing the hazardous waste immobilisation.